Pengaruh Undang Undang Cipta Kerja Terhadap Pemenuhan Upah Minimum Pekerja - Patrick Winson Salim; John Michael Hizkia; Rasji (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Wage determination is a crucial element in ensuring workers' rights, including their right to achieve a decent standard of living in line with human dignity. In alignment with this, the presence of the Job Creation Law represents a significant change in a country's labor law framework, aimed at promoting investment and economic growth. However, these changes also potentially impact worker wages, especially concerning the setting of minimum wages that depend on economic and labor market conditions. In this context, the determination of minimum wages must adhere to specific criteria. The conduct of this research aims to address the main issue,